Killer cell immunoglobulin receptors and T cell receptors bind peptide-major histocompatibility complex class I with distinct thermodynamic and kinetic properties. - Maenaka, K; Juji, T; Nakayama, T; Wyer, JR; Gao, G; Maenaka, T; Zaccai, N; Kikuchi, A; Yabe, T; Tokunaga, K; Tadokoro, K; Stuart, D; et al. (American Society for Biochemistry and Molecular Biology Inc., 1999)
Human natural killer cells and a subset of T cells express a repertoire of killer cell immunoglobulin receptors (KIRs) that recognize major histocompatibility complex (MHC) class I molecules. KIRs and T cell receptors (TCRs) bind in a peptide-dependent manner to overlapping regions of peptide-MHC class I complexes. KIRs with two immunoglobulin domains (KIR2Ds) recognize distinct subsets of HLA-C alleles. Here we use surface plasmon resonance to study the binding of soluble forms of KIR2DL1 and KIR2DL3 to several peptide-HLA-Cw7 complexes. KIR2DL3 bound to the HLA-Cw7 allele presenting the peptide RYRPGTVAL with a 1:1 stoichiometry and an affinity (K(d) approximately 7 microM at 25 degrees C) within the range of values measured for other cell-cell recognition molecules, including the TCR. Although KIR2DL1 is reported not to recognize the HLA-Cw7 allele in functional assays, it bound RYRPGTVAL/HLA-Cw7, albeit with a 10-20-fold lower affinity. TCR/peptide-MHC interactions are characterized by comparatively slow kinetics and unfavorable entropic changes (Willcox, B. E., Gao, G. F., Wyer, J. R. , Ladbury, J. E., Bell, J. I., Jakobsen, B. K., and van der Merwe, P. A. (1999) Immunity 10, 357-365), suggesting that binding is accompanied by conformational adjustments. In contrast, we show that KIR2DL3 binds RYRPGTVAL/HLA-Cw7 with fast kinetics and a favorable binding entropy, consistent with rigid body association. These results indicate that KIR/peptide-MHC class I interactions have properties typical of other cell-cell recognition molecules, and they highlight the unusual nature of TCR/peptide-MHC recognition.